2002
DOI: 10.1055/s-2002-34580
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Hypoplastic Left Heart Malformations: Norwood Palliation or Two-Ventricle Repair?

Abstract: Some anatomical subsets of HLHS with borderline mitral valves and small left ventricles may undergo two-ventricle repair despite severe LVOTO. Mortality and morbidity seem to be lower, but selection criteria are so far not defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Complete elimination of the left-to-right shunt by closing the atrial septal defect (ASD) has been suggested to reduce the risk of low cardiac output due to excessive left-to-right shunt through an unrestrictive communication. Improvement of left ventricular filling and therefore subsequent left ventricular growth is expected [ 1 , 10 , 11 ]. On the other hand, the sudden increase of preload may result in left ventricular overload and distension determining severe left ventricular dysfunction with sometimes a “stormy” early postoperative period [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete elimination of the left-to-right shunt by closing the atrial septal defect (ASD) has been suggested to reduce the risk of low cardiac output due to excessive left-to-right shunt through an unrestrictive communication. Improvement of left ventricular filling and therefore subsequent left ventricular growth is expected [ 1 , 10 , 11 ]. On the other hand, the sudden increase of preload may result in left ventricular overload and distension determining severe left ventricular dysfunction with sometimes a “stormy” early postoperative period [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the sudden increase of preload may result in left ventricular overload and distension determining severe left ventricular dysfunction with sometimes a “stormy” early postoperative period [ 1 , 9 , 10 ]. An alternative surgical option as a compromise between both approaches is the partial ASD-closure with a fenestrated patch [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the left ventricle in patients with hypoplastic left heart complex has been proved after biventricular type of repair, provided the accomplishment of complete relief of the systemic obstruction [35][36][37][38][39]. The preferred surgical technique is the reconstruction of the ascending aorta and aortic arch using either a pulmonary autograft or homograft.…”
Section: Hypoplastic Left Heart Complexmentioning
confidence: 99%
“…Since the neonatal left ventricle is already functioning at the plateau level of the Starling's curve, any volume overload can determine severe left ventricular dysfunction, and eventually death [38]. An alternative surgical option is the partial closure of the atrial septal defect: a fenestration allows a substantial reduction of the excessive left-to-right shunt in order to improve the left ventricular filling, and in the same time leaves enough time to the left ventricle to adapt to the new loading conditions [38,39].…”
Section: Hypoplastic Left Heart Complexmentioning
confidence: 99%
“…The difficult decision about univentricular as opposed to biventricular repair may be aided by fetal observations. 3,4 A vaginal delivery is preferable for infants with hypoplastic left heart syndrome, and avoids unnecessary risk for the mother as long as the fetus has no signs of cardiac failure. We use the cardiovascular profile score to select those fetuses requiring special attention, and we have shown that this cardiovascular score correlates with the Tei index.…”
Section: Prenatal Assessmentmentioning
confidence: 99%